Effect of 2-(3,4-Dichlorophenoxy)-triethylamine on the Synthensis of cis-Polyisoprene in Guayule Plants (Parthenium argentatum Gray) - Benedict, C. R. (1983)
The application of 2-(3,4-dichlorophenoxy)-triethylamine to guayule (Parthenium argentatum Gray var 593) plants results in a 2-fold stimulation of rubber synthesis and a 1.5- to 3-fold increase in mevalonic acid kinase, isopentenyl pyrophosphate isomerase, and rubber transferase. The increase in these enzymic activities accounts in part for the chemical induction of rubber synthesis.